Behind the veil : a critical analysis of European veiling laws - Cox, Neville, 1971- (Cheltenham (UK): Northampton (MA), USA Edward Elgar Publishing, 2019)
Since the early 2010s, an increasing number of European countries have passed laws that prohibit the wearing of various kinds of Islamic veil in particular circumstances. This insightful book considers the arguments used to justify such laws and analyses the legitimacy of these arguments both generally and in regards to whether such laws can be seen as justified interferences with the rights of women who wish to wear such garments.
Introduction -- Rationales for veiling and the meaning of the veil -- Veiling and rights -- Terrorism, national security and the Islamic veil -- Women's rights, equality and the Islamic veil -- Veiling and societal values -- Veiling and the rights of others -- Symbolic statements, clashing values and European anti-Veiling laws.
Includes bibliographical references and index.
Keywords: Hijab (Islamic clothing) -- Law and legislation -- Europe; Veils -- Religious aspects -- Islam; Hijab (Islamic clothing) -- Law and legislation; Veils -- Religious aspects -- Islam; Europe